1998
DOI: 10.1677/joe.0.1570127
|View full text |Cite
|
Sign up to set email alerts
|

Stress responsiveness of the pituitary-interrenal axis during early life stages of common carp (Cyprinus carpio)

Abstract: Whole-body levels of ACTH, -MSH and cortisol in eggs and larvae of the common carp (Cyprinus carpio) were determined periodically up until 168 h after fertilisation. ACTH, -MSH and cortisol immunoreactivity was detected in unfertilised eggs, and endogenous production of ACTH and -MSH was observed 24 h after fertilisation and that of cortisol 36 h after fertilisation. ACTH immunoreactivity reached peak levels before hatching (56-72 h after fertilisation) and remained relatively stable thereafter, while -MSH imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
0
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 35 publications
8
45
0
7
Order By: Relevance
“…In this respect Parhar (1997) showed that secretion of differentiated gonadotrophes during early developmental stages of Oreochromis mossambicus was arrested until GnRH fibers reached the pituitary gland. On the other hand, it was demonstrated that in the common carp Cyprinus carpio ACTH-and MSH-expressing cells were functional before hatching, a few hours after the first ir-cells were identified in the pituitary gland (Stouthart et al 1998). In accordance with these observations it is probable that synthesis and secretion of ADH hormones may be temporally separated in early developmental stages.…”
Section: Discussionmentioning
confidence: 59%
“…In this respect Parhar (1997) showed that secretion of differentiated gonadotrophes during early developmental stages of Oreochromis mossambicus was arrested until GnRH fibers reached the pituitary gland. On the other hand, it was demonstrated that in the common carp Cyprinus carpio ACTH-and MSH-expressing cells were functional before hatching, a few hours after the first ir-cells were identified in the pituitary gland (Stouthart et al 1998). In accordance with these observations it is probable that synthesis and secretion of ADH hormones may be temporally separated in early developmental stages.…”
Section: Discussionmentioning
confidence: 59%
“…In the chum salmon, 伪-MSH cells have been detected in the middle part of the pituitary 2 weeks before hatching (Naito et al 1993). In the common carp, 伪-MSH-and ACTHexpressing cells are functional before hatching (Stouthart et al 1998). In the ayu, 伪-MSH-and ACTH-expressing cells have been detected on the day of hatching (Saga et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…To exclude effects of handling stress (Stouthart et al 1998), seawater transfer was conducted by changing the water in the aquaria rather than moving the larvae. One day (24 h) after hatching, the osmolarity of one system was gradually but quickly (10 mosmol.min -1 ) increased by addition of artificial sea water, concentrated 3 times, to the water in the plastic aquaria to obtain a salinity of 650 mosmol.kg -1 (20%).…”
Section: Transfermentioning
confidence: 99%